Development Of UV monitoring system using metal oxide based sensor - Hafizuddin, Muhammad; Basor, Yasir Irsyad; Mohd Yusoff, Marmeezee; Mohd Razib, Mohd Asyraf; Malek, Mohd Firdaus; Mohamed, Ruziana; Kamarzaman, Azlin Haezrina (IET, 2022)
The development of ultraviolet (UV) monitoring system using metal oxide-based sensor has been experimented throughout the project. The metal oxide-based sensor used is the fabricated titanium dioxide nanorod arrays. The sensor is a self-powered UV photosensor that can generate a certain amount of voltage when the illumination of UV radiation exists on the surface of the sensor. Furthermore, the fabricated UV photosensor is designed based on photoelectrochemical (PEC) structure. The performance of the sensor has been experimented by manipulating the quantity of the thin film layer deposited on the surface of the sensor that is used as spacer and applying two different electrolytes that is the solution of salt water (Na2SO4) and mineral water in order to observe the generated output voltage with respect to the distance of UV source to the TiO2 UV photo sensor. Moreover, an Arduino board has been used for monitoring the amount of voltage generated from the photo sensor. The TiO2 UV photo sensor generated the voltage up to 0.3V with standard UV lamp that produces UV radiation wavelength of 365-400nm for a single layer of thin film, electrolytes of Na2SO4 and 5 cm distance of UV lamp from the sensor. Further experiments offer some beneficial results with respect to its properties, that leads to the basis of theoretical and experimental for better understanding of fundamental physics and extensive applications of titanium dioxide (TiO2) related structures